The order of adult emergence from a bean influences Callosobruchus maculatus biological parameters. (September 2022) - Amiri, Azam; Bandani, Ali R.
Abstract: We used a scramble-type strain of Callosobruchus maculatus to investigate the impact of cohabiting within the same host on biological parameters (adult longevity, fecundity, hatching percentage, and mating behaviors). In particular, we were interested in the impact of the order of adult emergence. Based on the results, the first emerging insect's biological parameters differ from the second emerging insect. The order of adult emergence significantly influenced fecundity, although it did not affect adult longevity. When two females cohabited in the same seed during immature development, the mating success of the first emerged female was higher (91.7%) than the second one (87.5%). Also, males were more reluctant to mate with the second one (10.4% compared to 6.2% in the first one). The second emerged females started to kick later to end mating, and their copulation duration lasted longer than the first female. When the female appeared sooner than her male cohabitant, other males' willingness to mate with these females decreased, and also, these females rejected no males. In males that exited sooner than another male in the bean, mating success decreased (78.0%) compared to the second emerged male (88.9%). In beans cohabiting a male and female larva, when the male appeared first, mating success increased to 100% compared to 89.8% in second emerged males. Although two cohabited insects that emerged as adults had not competed directly, we observed modifications in fecundity and mating behaviors such as fecundity, mating success, kick, and copulation duration. There was an indirect competition between two cohabitants of the seed that avoided direct competition. Highlights: The order of adult emergence significantly influenced fecundity. The mating success of the first emerged female was higher than the second one. Mating behaviors of the first emerged adult differ from the second one. Indirect competition between seed cohabitants that avoided direct competition.